The effect of wearing a custom-made mouthpiece on BMX performance - Smit, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: In BMX racing the start is very important. A good timing on the start signal and a high peak power output are important for a good start [1]. Recent studies suggest that wearing a custom-made mouthpiece which properly aligns and relaxes the jaw can improve anaerobic power output on a Wingate test in trained and highly trained athletes [2] and auditory and visual reaction time [3] in untrained subjects, although another recent study using a commercial mouthpiece did not find an effect on strength and power in recreationally trained men [4]. The purpose of this study was to determine if wearing a custom-made mouthpiece could instantly improve the start time in World Class BMX riders. METHODS: Five World Class BMX riders (3 men and 2 women) volunteered to participate in this study (age 22.2 ± 2.7 years old). A cross-over design with repeated measures was used. All measurements were executed in one session of 2.5 hours, with a custom-made mouthpiece randomly assigned. Each rider recorded seven correct trials with and without the mouthpiece. The time on the first downhill section of the track was measured. Times were averaged per rider for each condition. Magnitude-based inferences were used to determine probabilities of practical significance [5]. Effects were deemed unclear if the confidence interval overlapped the thresholds for both benefit and harm, and only effects greater than 75% likelihood were considered substantial. The smallest worthwhile change in performance was set at 0.5%. RESULTS: The mean time ± SD for the trials with the mouthpiece was 2.72 ± 0.11 s and without the mouthpiece 2.73 ± 0.10 s. The results showed a marginal effect for the mouthpiece for the average time over the seven trials. A 0.3% change in the mean (90% confidence limits: -0.2 to 0.8) was found, making it unlikely that the mouthpiece had a positive effect on the performance. DISCUSSION: No indication that wearing a custom-made mouthpiece has at least a small effect on BMX start performance in World Class BMX riders was found. A possible explanation for finding only a marginal effect is that in World Class athletes, the margin for improvement is so small, that interventions that have a large effect in untrained or trained persons, are likely to have a small effect in well trained and possibly a marginal effect in elite and World Class athletes. It can be concluded that wearing a custom-made mouthpiece has a marginal effect on BMX start performance in World Class BMX riders.